Pengaruh Elemen Tempo Dalam Gamelan Jawa Terhadap Respons Emosi Musikal - Djohan Djohan (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2008)
Intense personal experience that provide insight into the nature of life that involved emotion, cognitive, and social component happens when people listen to music. Those musical emotion responses are expressed when the aesthetical value of music comes toward either through everyday music listening, or through intended performances. Therefore, this basic experimental research was proposed to examined Javanese subjects, using the Javanese gamelan musical instrument, and was conducted in Yogyakarta. The purpose of the experiment was to obtain a better picture on how the element of tempo stimulation influence the musical emotional responses of its listener.There were 32 subjects (musicians and non musicians) who are participating in this experiment. The study found that effect of unmodified and modified tempo element towards the musical emotional responses of the musicians differs from those of non-musician. There are definitely differences provided by effect of the tempo element stimulation towards the emotional musical responses of the listeners, as well as showing that tempo is the most important element and potentially stimulate emotional musical responses. Key words     :  Javanese gamelan, tempo, emotional musical responses.